Expression pattern of Calbindin-D28k, NeuN proteins, ATOH1 and EN2 genes in the human fetal cerebellum - Phanindra Prasad Poudel; Arnab Ghosh; Chacchu Bhattarai; Saman Pradhan; Nirmal Panthi; Dela Singh Joshi; Shanti Khadka; Sandhya Kumari; Guruprasad Kalthur; R. Vani Lakshmi; Sneha Guruprasad Kalthur (Translational Research in Anatomy)
Background: Human cerebellum plays a crucial role in motor coordination and cognitive functions. Series of events such as cell proliferation, migration, and differentiation occur during the development, which are tightly regulated by specific genes. Understanding the expression patterns of key genes involved in these processes during various stages of fetal development can provide valuable insights into the complex mechanisms of cerebellar development. This study aims to investigate the expression patterns of Calbindin-D28k, NeuN (neuronal nuclease), ATOH1 (Atonal homolog 1), and EN2 (Engrailed -2) in the human fetal cerebellum. Methods: This is a descriptive observational study carried out in human fetal cerebellum, fluorescent immunohistochemistry was performed to study the expression of Calbindin-D28k and NeuN, and while the expression of ATOH1 and EN2 genes were quantified with the help of qPCR. Results: Calbindin-D28k was highly immunoreactive in the Purkinje cells and located in their cytoplasm, nucleus and dendrites whereas absent in their axons. NeuN was expressed weakly in the perinuclear cytoplasm and nucleus of granule cells whereas absent in their dendrites and axons. ATOH1 gene was upregulated during third trimester whereas EN2 gene was upregulated during second as well as third trimesters. Conclusion: Distribution and intensity of Calbindin-D28k and NeuN proteins in the human fetal cerebellum increased with the increase in fetal age. Expression pattern of ATOH1 and EN2 genes indicated that second and third trimesters are the crucial periods for the proliferation, migration and maturation of granule cells. These genes may play a crucial role in the establishment of normal morphology of human fetal cerebellum and its development.